Two-Way Symmetrical Model in Enhancing Inclusivity: A Case Study of Sunyi Coffee - Erika Kezhia Josephine; Nicholas Ronald Parris; Rawi Diwangkara Harrianto (Institut Komunikasi dan Bisnis LSPR, 2024)
Inclusivity in Indonesia, especially in Jakarta, is starting to become a visible issue and is starting to be noticed. This issue is not only from a social perspective, but also from a work perspective. Jobs are now starting to employ people with disabilities, but the number is not large and there are still many people who are not used to interacting with people with disabilities because of the social stigma related to disability. This study explores the role of public relations in promoting inclusivity and fostering engagement between deaf employees and customers at Sunyi Coffee, a socially conscious café in Indonesia. Guided by the Two-Way Symmetrical Model, the research analyzes gaps in interactions and provides actionable recommendations for future strategies. Using qualitative methods, including interviews, observations, and case analysis, this study emphasizes the importance of open communication in building a vibrant and inclusive digital community. The findings offer practical insights for organizations aiming to enhance inclusivity and customer relationships through digital platforms.